Proposing a Frame of Ethical Principles for Educational Evaluation in Modern Greece - Tsitas, Georgios; Verdis, Athanasios (Conatus - Journal of Philosophy, 2021)
In a country with a long philosophical tradition like Greece, the lack of Ethical Principles for educational evaluation is surprising. This article presents the reasons for such a gap within the general theoretical framework for educational evaluation, combined with major schools of thought on Ethics. The authors discuss the importance for educational evaluation and assessment and take a critical view of present ethical frames. They proceed to fill the gap by coming up with a list of twenty-seven Ethical Principles, the result of the varying consensus of sixteen Greek assessment experts, upon the researcher’s initial proposals. The Delphi Method, that was employed to formulate the list, is described and the first complete Ethical frame of educational evaluation for modern Greece is proposed.